Demographic Variables and its Relationship to Work Life Balance A study of Doctors in Government Hospitals of Himachal Pradesh - Sharma, Sakshi; Parmar, Jai Singh; Chauhan, S. S. (Gyan Management Journal, 2015)
The modern organizations are operating in the environment which is entirely different from the past decades where men dominated the workforce in the factories and the household work was taken care of by the women. ln the rapidly changing environment a large number of women have entered the workforce, which makes the global labor market structure changed. The family structure is moving from traditional single-income family to dual-career family. This trend has enhanced the child and elder care burden on a large number of employees and in addition has created new challenges for them in balancing their work and family life. Therefore, the present study was designed to analyse the relationship between demographic variables and work life balance and its dimensions, namely work interference with personal life, personal life interference with work and work/personal life enhancement. The study sought to determine whether age, gender and marital status had any relationship with work life balance and its dimensions. The study was conducted through the sample of 141 doctors employed in various government hospitals of Himachal Pradesh. The data thus collected have been analyzed with the help of SPSS 17. In order to analyze the data the statistical tools viz. Pearson correlation coefficient and Independent sample t-testwere used.
Keywords: work life balance; demographic variables; work-family conflict; work life enhancement